Social inequality in phase II cardiac rehabilitation attendance: The impact of potential mediators. (April 2018) - Pedersen, Maria; Egerod, Ingrid; Overgaard, Dorthe; Baastrup, Marie; Andersen, Ingelise
Background: Cardiac rehabilitation participation is an essential component of the contemporary management of coronary heart disease. However, patients with low socioeconomic position are less likely to attend the rehabilitation programme. Aim: We aimed to explore the effect of potential mediators between socioeconomic position defined by educational attainment and cardiac rehabilitation attendance. Methods: Prospective observational study of patients with acute coronary syndrome ( N =302). Logistic regression and mediation analysis was conducted to explore mechanisms of non-attendance. Results: Thirty per cent attended full cardiac rehabilitation. Patients with low educational attainment, comorbidities, long commute to cardiac rehabilitation centre, and lone dwelling were less likely to attend full cardiac rehabilitation, whereas patients with high anxiety and depression score were more likely to attend full cardiac rehabilitation. Patients with low educational attainment had lower self-efficacy and longer commute compared with patients with high educational attainment. The potential mediators included in the study, however, did not have a significant mediation effect. Conclusion: Our study demonstrated a variety of mechanisms contributing to cardiac rehabilitation non-attendance. Further, the study demonstrated that non-attendance was especially related to the cardiac rehabilitation elements involving lifestyle modifications. However, the mechanisms explaining social inequality in full cardiac rehabilitation are still not fully understood.